SEISMOLOGICAL MONITORING OF THE DEFORMATION PROCESS - Bormotov V.A.; Bykov V.G. (My University, 2001)
A technique for determining volume deformation variations is suggested and substantiated theoretically on the basis of the multiple-reflection longitudinal waves specified in the seismograms from distant earthquakes. Results of seismological monitoring carried out in the south of Priamurye testify to the qualitative and quantitative difference of the deformation process at different depth levels. Variations of volume deformation are estimated down to a depth of 50 km.